Growth and phosphorus uptake of potato (Solanum tuberosum L.) in an alkaline soil as affected by mineral nitrogen forms and inoculation with phosphate-solubilizing bacteria and mycorrhizal fungi - Weimers, Kristina (SLU/Dept. of Biosystems and Technology (from 130101), 2017)
In soils with relatively high pH (pH > 7), potatoes (Solanum tuberosum L.) and other phosphorus (P) demanding crops might suffer from P deficiency despite P fertilization and significant reserves of P in the soil. Also, a high risk for P deficiency for potatoes may be expected when the soil is cold and the root system undeveloped. Therefore, the risk of Plimitation in high-pH soils is probably greatest for early varieties. In this study a trial was set up with two objectives: (i) To assess the effect of ammonium sulphate (T1) on P uptake, vegetative growth and tuber yield in potatoes grown without addition of P in soils with relatively high pH (7.5) and P-AL class IVB (12.5 mg P/100 g soil), under climatic conditions similar to those for early potatoes in the south of Sweden. The effect of ammonium sulphate was compared with the effect of ammonium nitrate (T2), ammonium chloride (T3) and potassium nitrate (T4). (ii) To assess the impact of inoculation with spores of arbuscular mycorrhizal fungi (AMF) Rhizophagus irregularis (T5) and the phosphorus solubilizing bacteria (PSB) Bacillus megaterium (T6) on the said parameters and under the same conditions. The trial was limited to the early potato variety ‘Solist’ grown with one level of nitrogen fertilizer. After harvesting, data was collected on fresh and dry matter and shoots and tubers were analysed for P content. The potato plants in the trial did not reach full maturity, probably due to salt toxicity, which made any possible differences between the treatments difficult to discern. At harvest the P concentration in all plants in all treatments was lower than normal levels. No significant differences were found between treatments on the effect on total dry weight of tubers or shoots. Also, no significant differences were found between treatments in number of tubers produced. The plants which received ammonium chloride (T3) had a significant smaller concentration of P compared to T1, T2 and T5. The difference can probably be explained by the fact that T3 had the highest salt concentration of all treatments. AMF colonization in the roots were found in all pots in both the control T2 and the inoculated T5. In conclusion, the result did not support the hypothesis that it would be possible to control P availability for early potatoes, grown in alkaline soils with relatively high P content, through the choice of nitrogen source or through inoculation with PSB or AMF.